Adiposity measures and arterial stiffness in primary care: the MARK prospective observational study. Issue 9 (27th September 2017) - Gomez-Sanchez, Leticia; Garcia-Ortiz, Luis; Patino-Alonso, Maria C; Recio-Rodriguez, Jose I; Rigo, Fernando; Martí, Ruth; Agudo-Conde, Cristina; Rodriguez-Sanchez, Emiliano; Maderuelo-Fernandez, Jose A; Ramos, Rafel; Gomez-Marcos, Manuel A
Abstract : Background: The cardiovascular risk of obesity is potentially increased by arterial stiffness. Objective: To assess the relationship of adiposity measures with arterial stiffness in Caucasian adults with intermediate cardiovascular risk. Setting: Six Spanish health centres. Participants: We enrolled 2354 adults (age range, 35–74 years; mean age, 61.4±7.7 years, 61.9% male). Methods: This is a cross-sectional study that analyses data from the baseline visit of the improving interMediAte RisK management (MARK) study. The main outcome variables were body mass index (BMI), waist-to-height ratio (WHtR), Clínica Universidad de Navarra-body adiposity estimation (CUN-BAE) body fat percentage and body roundness index (BRI). Vascular function was assessed by the cardio-ankle vascular index (CAVI) with the VaSera device; brachial-ankle pulse wave velocity (baPWV) was determined using a validated equation. Results: The mean adiposity measures were a BMI of 29.2±4.4, WHtR of 0.61±0.07, CUN-BAE of 35.7±1.7 and BRI of 5.8±1.7. The mean stiffness measures were a CAVI of 8.8±1.2 and baPWV of 14.9±2.5. In multiple linear regression analyses, all adiposity measures were negatively associated with CAVI and baPWV (p<0.01 for all) after adjustment for possible factors of confusion. The proportion of CAVI variability via the adiposity measures were 5.5% for BMI, 5.8% for CUN-BAE, 3.8% for WHtR and 3.7% for BRI. These were higher among diabetic, obese, younger (≤62 years) and non-hypertensive subjects who had similar activity and sedentary profiles. Conclusions: Adiposity measures are negatively associated with arterial stiffness measures. The percentage of variation in CAVI explained by its relation to the different measures of adiposity ranges from 5.8% (CUN-BAE) to 3.7% (BRI). In the case of baPWV, it oscillates between 0.7% (CUN-BAE and BMI) and 0.1% (WHtR). Trial registration number: NCT01428934.